Toxic effects of pesticides on land mammals - Baltazar Vilcarano, Yahaida (2025)
Pesticides, such as organophosphates, carbamates, and pyrethroids,are common agricultural chemicals that can affect health andthe environment. Organochlorines and DPCs (polychlorinatedbiphenyls) cause bioaccumulation and adverse toxic effects inmammals. Their worldwide use and risks persist despite bans. Asystematic review was conducted following the PRISMA method,searching for articles from 2018 to 2024 in ScienceDirect andGoogle Scholar with the keywords “pesticides” AND “toxicity”AND “mammals”. 46 articles that met the inclusion criteria ontoxic effects in mammals were selected. Various studies evaluatingthe toxic effects of pesticides on mammals were identified. Mostof the articles were published in 2024 (11) and 2023 (12). China and Japan led in publications, followed by India, the United States,and Türkiye. Rattus norvegicus “rat” was the most studied species,with 26 studies, followed by Mus musculus “mouse”, Sus scrofadomestica “pig” and Oryctolagus cuniculus “rabbit”. A total of 72 typesof pesticides were investigated, the most notable being: chlorpyrifos,organochlorines, tebuconazole, imidacloprid, cypermethrin,glyphosate, neonicotinoids, thiamethoxam deltamethrin, pirimiphosand clothianidin. Chlorpyrifos was identified as the most used inresearch on terrestrial mammals. Exposure to pesticides can causeneurological, hepatic and reproductive effects in mammals. Advancesin molecular biology have improved research into these effects,with chlorpyrifos standing out for its reproductive and neurologicaldamage.